Reflections of Mentoring for Indigenous Youth In the Fourth R - Trovarello, Elisa (Scholarship@Western, 2019)
The purpose of this qualitative study was to investigate the reflections of peer mentors and mentees over time who have participated in the Fourth R: Uniting Our Nations Peer Mentoring Program. Data was collected from five youth mentors, four of whom also participated as mentees, via interviews utilizing a narrative based methodology in which story-telling and meaning-making was encouraged through the interview guide and procedure. Thematic content analysis of the data was conducted manually and revealed five key themes: 1) Cultural Connection, increases in 2) Intrapersonal Skills, 3) Interpersonal skills, 4) Social support, and 5) Education and Career Benefits. The findings indicated that Indigenous youth post program involvement carried forward similar benefits to those previously reported in the Fourth R, including cultural connection based activity and engagement, as well as impacts on intrapersonal development such as confidence and leadership skills. The findings also indicate that benefits may transform in post-graduation as participants reported continued instances of mentoring others, as well as becoming more involved in Indigenous oriented advocacy and the desire to pursue further education and career goals. Specifically, a more nuanced meaning-making approach concerning their own personal understanding of culture was identified. This study contributes to strength-based research that underlines the importance of culturally relevant programming that puts Indigenous youth at the forefront and empowers cultural connection as well as personal development.